Public Perceptions of Political Phenomena Without Vote Buying: Study on The 2020 Local Election - Tirta Pandu Winata (International Forum of Researchers and Lecturers, 2024)
Vote buying is a phenomenon that is often found in the arena of political contestation. However, there is a unique phenomenon in the 2020 Regional Head Election for Wonosobo Regency, which consists of one pair of candidates against an empty box. In the election (Pilkada), there was no indication of its use of money politics or vote buying, either by the candidate pair or the empty box support team. This study aims to analyze the perceptions of the people of Wonosobo Regency, who are familiar with the phenomenon of vote buying but have yet to find it in the 2020 Pilkada. The research method used in this study is a qualitative method with a descriptive approach. The results of this study indicate that three main components become symptoms and can indicate public perceptions of their absence of vote buying in the Pilkada of Wonosobo Regency in 2020. First, the cognitive component includes public knowledge and its implications for the view that there is no vote buying. Second, the affective component indicates a positive emotional aspect of vote buying. Third, the cognitive component that influences positive action after the above expectations of vote buying are not fulfilled.